A model for photothermal conversion of graphene-filled nanocomposites under NIR irradiation. (16th November 2020) - Li, Fang; Wang, Lanlan; Tian, Hongyan; Zhang, Haiyu; Lin, Yongshui
Abstract: Graphene, acted as an excellent photothermal inorganic filler in photothermal smart composites, has triggered the fast increasing research upsurge in biomedical imaging, photothermal therapy, photothermal driving and so on recently. Many studies have shown that a low mass loading graphene nanosheets (GNSs) in a matrix can provide the nanocomposite with high photothermal conversion efficiency in the near-infrared (NIR) region due to its strong NIR adsorption and high thermal conductivity. Aiming to indicate the photothermal conversion mechanism, we present an analytical approach based on the Maxwell electromagnetic wave theory, thermodynamics method and effective medium approximation. The influence mechanism of graphene concentration and size, light intensity of NIR irradiation, interfacial thermal resistance between graphene and matrix on the photothermal conversion are all explained in this paper.